2016
DOI: 10.1038/hr.2016.28
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ACE2 deficiency on physical performance and physiological adaptations of cardiac and skeletal muscle to exercise

Abstract: The renin-angiotensin system (RAS) is related to physiological adaptations induced by exercise. Angiotensin-converting enzyme (ACE) 2 is a major regulator of the RAS in tissues, as it metabolizes angiotensin (Ang) II to Ang-(1-7). The aim of this study was to determine the effects of ACE2 deficiency on physical performance and physiological adaptations induced by voluntary running. Physical performance, body composition and plasma angiotensin levels, as well as tissue morphology and gene expression of RAS comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 37 publications
0
41
0
1
Order By: Relevance
“…Although running less, ACE2-deficient mice in our study ran continuously every night. As shown for WT mice, long-term voluntary wheel running leads to alterations in muscle strength (e.g., increased muscle mass and skeletal muscle hypertrophy) that was abolished in ACE2-deficient mice [34]. Skeletal muscle releases cathepsin B during longterm treadmill running in monkeys that might affect brain function [35].…”
Section: Discussionmentioning
confidence: 98%
“…Although running less, ACE2-deficient mice in our study ran continuously every night. As shown for WT mice, long-term voluntary wheel running leads to alterations in muscle strength (e.g., increased muscle mass and skeletal muscle hypertrophy) that was abolished in ACE2-deficient mice [34]. Skeletal muscle releases cathepsin B during longterm treadmill running in monkeys that might affect brain function [35].…”
Section: Discussionmentioning
confidence: 98%
“…Riquelme et al (446) suggested that the expression of ACE2 regulates fibrosis in dystrophic muscle since muscle damage causes increased activity of ACE2, and ACE2 levels correlate with the degree of fibrosis. Recently it has been reported that ACE2 -/y mice show reduced performance in voluntary running (380), but it is unknown whether this is a result of the genetic deletion of ACE2 in muscle cells, considering that this mouse exhibits an overall deficiency in ACE2.…”
Section: G Skeletal Muscle Systemmentioning
confidence: 99%
“…This review will summarize how animals with targeted alterations in ACE2 expression have helped to reveal its physiological and pathophysiological functions in particular in the central nervous system. The same and additional models have also been used to discover that ACE2 is a major determinant in cardiac [24,[30][31][32] and vascular function [33][34][35], atherosclerosis [36][37][38][39], metabolism [37,40], kidney [41][42][43][44] and lung diseases [45,46], to only name a few. However, these peripheral actions of ACE2 have previously been reviewed and are therefore not subject of this paper [19,[47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%